Fenología de los estados vegetativos de mandioca (Manihot esculenta Crantz) en base al tiempo térmico - Burgos, Ángela María; Prause, Juan; Argüello , Juan Alberto; Cenóz, Pedro Jorge (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2022)
Cassava (Manihot esculenta Crantz) is the fourth largest source of calories in the human diet, is also suitable for animal feed and biofuel extraction. This article aims to evaluate the performance of a thermal time (TT) model in order to characterize the phenological phases (FF) of two cassava cultivars in a growth cycle of 280 days, grown under field conditions in Corrientes, Argentina. Phenological observations were done during the years 2007/2008 and 2008/2009. The TT calculation was based on the residual method; the base temperature was 16°C. Differences between cultivars were observed in the degree-days (GD) accumulated to comply the expansion of the first (00-01) and ninth leaf (00-02 H9) FF, and in the thickening of roots (00-04 ERR), the latter related to the leaf area index (IAF). To complete the growth cycle the cultivars Palomita and Amarilla required around 2027 and 2096 GD respectively. The growth pattern and phenological development of the cultivars based on the accumulated GD, can be used to characterize the progress of the crop in Corrientes environment.